Comparison of Neural Activity in Chronic Pain Patients During Tonic and Burst Spinal Cord Stimulation Using Fluorodeoxyglucose Positron Emission Tomography. Issue 1 (30th April 2019) - Yearwood, Thomas; De Ridder, Dirk; Yoo, Hye Bin; Falowski, Steven; Venkatesan, Lalit; Ting To, Wing; Vanneste, Sven
Abstract : Objective: Burst spinal cord stimulation (SCS) is a novel stimulation paradigm that seems to provide better pain relief compared to the classic tonic SCS with minimal paresthesia sensation. Based on source localized electroencephalography and clinical data, it has been proposed that burst stimulation as defined by Dirk De Ridder exerts this greater effect by not only modulating the lateral and the descending pain‐inhibitory pathways (similar to tonic SCS) but also modulating the medial pain pathway, which encodes the affective, motivational aspects of pain. Material and Methods: The current study evaluates the supraspinal differences between burst and tonic stimulation with another functional imaging technique, namely fluorodeoxyglucose positron emission tomography (FGD‐PET) scanning, in seven patients, who underwent both burst and tonic SCS, to confirm this notion of medial pain pathway modulation. Results: The results of the current FGD‐PET study show that burst stimulation, in contrast to tonic stimulation, indeed modulates the dorsal anterior cingulate cortex (i.e., medial pain pathway) more than tonic stimulation. Discussion: Our data suggest an inherent difference in the central neural mechanisms during burst and tonic stimulation, which could potentially alter the patient's perception of pain. Conflict of Interest: Dr. Yearwood, Dr. De Ridder, Dr. Falowski, and Dr. Vanneste are the consultants of Abbott. Dr. Venkatesan is an employee of Abbott. Hye Bin Yoo and Dr. Wing Ting To have no conflicts of interest to report.